Lichenysin Production by Bacillus licheniformis Food Isolates and Toxicity to Human Cells - Yeak, Kah Yen Claire; Perko, Manca; Staring, Guido; Fernandez-Ciruelos, Blanca M.; Wells, Jerry M.; Abee, Tjakko; Wells-Bennik, Marjon H. J. (Frontiers in Microbiology, 2022)
Bacillus licheniformis can cause foodborne intoxication due to the production of the surfactant lichenysin. The aim of this study was to measure the production of lichenysin by food isolates of B. lichenformis in LB medium and skimmed milk and its cytotoxicity for intestinal cells. Out of 11 B. licheniformis isolates tested, most showed robust growth in high salt (1M NaCl), 4% ethanol, at 37°C or 55°C, and aerobic and anaerobic conditions. All strains produced lichenysin (in varying amounts), but not all strains were hemolytic. Production of this stable compound by selected strains (high producers B4094 and B4123, and type strain DSM13T) was subsequently determined using LB medium and milk, at 37°C and 55°C. Lichenysin production in LB broth and milk was not detected at cell densities < 5 log10 CFU/ml. The highest concentrations were found in the stationary phase of growth. Total production of lichenysin was 4-20 times lower in milk than in LB broth (maximum 36 µg/ml), and 10 times lower in the biomass obtained from milk agar than LB agar. Under all conditions tested, strain B4094 consistently yielded the highest amounts. Besides strain variation and medium composition, temperature also had an effect on lichenysin production, with two-fold lower amounts of lichenysin produced at 55°C than at 37°C. All three strains produced lichenysin A with varying acyl chain lengths (C11 to C18). The relative abundance of the C14 variant was highest in milk and the C15 variant highest in LB. The concentration of lichenysin needed to reduce cell viability by 50% (IC50) was 16.6 µg/ml for Caco-2 human intestinal epithelial cells and 16.8 µg/ml for pig ileum organoids. Taken together, the presence of low levels (< 5 log10 CFU/ml) of B. licheniformis in foods is unlikely to pose a foodborne hazard related to lichenysin production. However, depending on the strain present, the composition, and storage condition of the food, a risk of foodborne intoxication may arise if growth to high levels is supported and such product is ingested.